Adsorption of ionic and neutral pharmaceuticals and endocrine-disrupting chemicals on activated carbon fiber: batch isotherm and modeling studies. (April 2023) - Zhao, Yufeng; Wu, Guiping; Wei, Wei; Song, Myung-Hee; Cho, Chul-Woong; Yun, Yeoung-Sang
Abstract: Activated carbon fiber (ACF) has received increasing attention as an adsorbent due to its excellent surface properties. However, the adsorption mechanism of ACF for micropollutants, especially those in ionic forms, has not been sufficiently characterized to date. Therefore, the adsorption property of ACF was characterized using isotherm experiments and linear free energy relationship (LFER). For the experiments, adsorption affinities of thirty-five chemicals, i.e., pharmaceuticals and endocrine-disrupting chemicals, on ACF were estimated. Afterward, the adsorption affinities were used as dependent variables to build the LFER modeling. Finally, three isolated models for each chemical species, i.e., cations, anions, and neutrals, and a comprehensive model for the whole dataset were developed. The LFER results revealed that the models for anionic and neutral compounds have high predictabilities in R 2 of 0.97 and 0.96, respectively, while that for cations has a slightly lower R 2 of 0.72. In the comprehensive model including cationic, anionic, and neutral compounds, the accuracy of it is 0.81. From the developed LFER model based on the whole dataset, the adsorption mechanisms of ACF for the selected substances could be interpreted, in which the terms of hydrophobic interaction, hydrogen bonding basicity, and anionic Coulombic force of the compounds were identified as the predominant interactions with ACF. Graphical abstract: Image 1 Highlights: ACF adsorbs pharmaceutical-based emerging contaminants with different charges. Adsorption of micropollutants by ACF could be predicted using the LFER model. The developed models have high predictability for anionic and neutral compounds. The π-π interaction as the main driving force for cations is stronger than for anions and neutrals.